Prioritizing Renewable Energy Systems in Ethiopia: A Fuzzy TOPSIS Framework Incorporating Climate Vulnerability and Grid Constraints - Abel Berhanu Sitotaw; Belay Sitotaw Goshu (Britain International for Academic Research (BIAR) Publisher, 2026)
Ethiopia derives approximately 98% of its electricity from renewable sources, predominantly hydropower. However, climate-induced droughts increasingly threaten hydropower reliability, while grid infrastructure limitations constrain variable renewable integration. Existing energy planning lacks a systematic framework to balance these competing priorities under uncertainty. Purpose: This study develops a fuzzy TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) framework to prioritize five renewable energy systems large hydropower, wind, solar PV, hybrid solar-wind-battery, and geothermal for Ethiopia, explicitly incorporating climate vulnerability and grid constraints alongside technical, economic, environmental, socio-political, and risk criteria. Method: Triangular fuzzy numbers capture linguistic assessments from policy documents and stakeholder input. Fifteen sub-criteria are evaluated using fuzzy TOPSIS, with criteria weights derived from Ethiopian policy analysis emphasizing climate resilience and grid expansion. Sensitivity analyses test weight variations. Findings: Under baseline weighting (very high climate vulnerability weight), wind ranks first (closeness coefficient 0.645), followed by geothermal (0.614), hybrid (0.559), solar PV (0.506), and large hydropower (0.369). Hydropower’s low ranking results from extreme climate vulnerability, water consumption, and land use penalties. Sensitivity analysis shows hybrid systems become more competitive as grid constraint weight increases, while hydropower’s rank declines further when climate risk is emphasized. Conclusion: Incorporating climate vulnerability fundamentally reverses conventional hydropower-first prioritization. Diversification toward wind, geothermal, and hybrid-battery systems is essential for climate-resilient energy planning. Recommendation: Ethiopian policymakers should cap new large hydropower, accelerate wind and geothermal deployment, and promote hybrid storage solutions for weak-grid areas.